Spatial Coupling Pattern of Soil Layer and Upper Epikarst Zone on a Dolomite Hillslope - TANG Xufang; FU Zhiyong; HUANG Yuhan; WANG Sheng; ZHAO Jie; CHEN Hongsong (Shuitu Baochi Xuebao)
[Objective] Restoring vegetation and combating rocky desertification on dolomite slopes in karst regions face significant challenges. The upper epikarst zone, which underlies the shallow soil layer, plays a crucial role in ecosystem processes. Nevertheless, the coupling relationships between the soil and the upper epikarst zone remain poorly understood. [Methods] A representative dolomite hillslope was chosen for detailed soil-epikarst system structure investigation through trench excavation method. By integrating Kriging interpolation with geographically weighted regression analysis, the spatial distribution characteristics of different medium layers in the soil-epikarst system were analyzed. The study preliminarily proved the co-evolving feature of the soil and the underlying upper epikarst zone on dolomite hillslopes. [Results] 1) The thickness of soil and upper epikarst zone on the dolomite hillslope gradually increased down the slope. The average thickness of the upper epikarst zone on a hillslope scale was 50 cm, with an average volume of 0.47 m3/m2, accounting for 43.9% of the total volume of the soil profile, indicating that the ecological function of epikarst in karst regions is extremely important. 2) The soil-epikarst system′s structure of the dolomite hillslope exhibited strong spatial heterogeneity. The spatial heterogeneity of the underlying upper epikarst zone (C+C0=18.88) was significantly higher than that of the overlying soil layer (C+C0=15.84); 3) The overall soil thickness, especially the B horizon′s thickness, was significantly positively correlated with the upper epikarst zone′s weathering degree, indicating that the increase of soil thickness promoted the weathering of the underlying upper epikarst zone, and there was a clear coupling and collaborative development relationship between soil and upper epikarst zone. [Conclusion] The soil and upper epikarst zone in karst regions have evolved in a mutually reinforcing manner. The upper epikarst zone acts as an essential substrate for supporting the karst ecosystem. The soil thickness, especially the B horizon′ thickness, may be critical parameters for predicting epikarst depth on karst hillslopes. In karst areas, the underlying carbonate rocks can not be ignored when carrying out soil and water resources evaluation.